Defective anterograde protein-trafficking contributes to endoplasmic reticulum-stress in a CLN1 disease model - Nisha Plavelil; Abhilash P. Appu; K.C. Gopal; Avisek Mondal; Neil Perkins; Anil B. Mukherjee (Neurobiology of Disease)
Lysosomal storage disorders (LSDs) represent 70 inherited metabolic diseases, in most of which neurodegeneration is a devastating manifestation. The CLN1 disease is a fatal neurodegenerative LSD, caused by inactivating mutations in the CLN1 gene encoding palmitoyl-protein thioesterase-1 (PPT1). S-palmitoylation, a reversable posttranslational modification by saturated fatty acids (generally palmitate) facilitates endosomal trafficking of many proteins, especially in the brain. While palmitoyl-acyltransferases (called ZDHHCs) catalyze S-palmitoylation, depalmitoylation is mediated by palmitoyl-protein thioesterases (PPTs). We previously reported that in Cln1−/− mice, which mimic human CLN1-disease, endoplasmic reticulum (ER)-stress leads to unfolded protein response (UPR) contributing to neurodegeneration. However, the mechanism underlying ER-stress has remained elusive. The anterograde (ER to Golgi) protein-trafficking is mediated via COPII (coat protein complex II) vesicles, whereas the retrograde transport (Golgi to ER) is mediated by COPI vesicles. We hypothesized that dysregulated anterograde protein-trafficking causing stagnation of proteins in the ER leads to ER-stress in Cln1−/− mice. We found that the levels of five COPII vesicle-associated proteins (i.e. Sar1, Sec23, Sec24, Sec13 and Sec31) are significantly higher in the ER-fractions of cortical tissues from Cln1−/− mice compared with those from their WT littermates. Remarkably, all COPII proteins, except Sec13, undergo S-palmitoylation. Moreover, CLN8, a Batten disease-protein, requires dynamic S-palmitoylation (palmitoylation-depalmitoylation) for ER-Golgi trafficking. Intriguingly, Ppt1-deficiency in Cln1−/− mice impairs ER-Golgi trafficking of Cln8-protein along with several other COPII-associated proteins. We propose that impaired anterograde trafficking causes excessive accumulation of proteins in the ER causing ER-stress and UPR contributing to neurodegeneration in CLN1 disease.